Dramatic improvement in severe-critical COVID-19 patient after tocilizumab administration: a clinical experience - Yesicha Kurniawati; Kadek Surya Atmaja; Ketut Suryana; Wayan Wahyu Semara Putra (Intisari Sains Medis, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in coronavirus disease 2019 (COVID-19) involve so many inflammatory cytokines, especially Interleukin-6 (IL-6). The usage of tocilizumab as an anti-IL-6 receptor antibody had been approved as COVID-19 medication.Case Presentation: This article reports a 51-year-old woman diagnosed with severe-critical COVID-19. The patient made significant progress after tocilizumab administration. The patient was hospitalized for 14 days before being discharged.Conclusion: Tocilizumab administration showed a significant improvement in COVID-19 patients.  However, further investigations are needed to explain this further.